COMPARISON OF DIAGNOSTIC ACCURACY OF TRANSPERINEAL SONOGRAPHY WITH THE TRANSVAGINAL ULTRASONOGRAPHY IN DETERMINING ACCURATE CERVICAL LENGTH - Usman, Arooba; Shafique, Mobeen; Jalil, Jawad; Amin, Umar; Zafar, Saerah Iffat; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2019)
Objective:To evaluate the diagnostic accuracy of transperineal ultrasonography in assessing the accurate cervical length at 24-32 weeks of gestation in comparison with the TVS as gold standard.Study Design: Cross sectional study.Place and Duration of Study: Department of Radiology, CMH Multan, from 12th Apr 2014 to 11th Dec 2014. Material and Methods:A total of 157 patients of 20-35 years of age with singleton pregnancy of gestational age 24 to 32 weeks were included in the study. Patients with premature rupture of membrane, cervical incompetence, cervical injury, multiparity and h/o co-morbid conditions were excluded. Cervical length was measured first by transperineal ultrasound followed by trans-vaginal ultrasound.Results:Of the total 157 patients assessed, 96 were true positive, 4 were false positive, 13 were false negative and 44 were true negative. Among 57 transperineal ultrasound negative patients, 13 (False Negative) had short cervical length on trans-vaginal sonography where as 44 (True Negative) had normal length. So, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of transperineal sonography in assessing accurate cervical length are 88.07%, 91.67%, 96.0%, 77.19% and 89.17% respectively. Conclusion:This study concluded that transperineal sonography is a reliable, easily available and cost effective method with high diagnostic accuracy for assessing the cervical length at 24-32 weeks of gestation which nearly approaches the value of trans-vaginal sonography.